1995
DOI: 10.1007/bf01839310
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the effect of dietary supplementation with cod liver oil on the polyunsaturated fatty acid composition of boar semen

Abstract: Eight mature Norwegian Landrace boars, of proven fertility and in routine semen production for AI, were fed individually with the same basic diet for 9 weeks. One group of 4 animals served as the control, the remaining 4 boars received a daily supplement of 75 ml cod liver oil (CLO-group). Fifteen consecutive semen samples were collected from each boar. The fatty acid composition of the semen was determined, and the content of the 15 most numerous fatty acids with a chain length longer than 12 carbon atoms was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 23 publications
2
19
1
3
Order By: Relevance
“…Many authors [6][7][8][9] have reported that dietary supplementation with LCP n-3 fatty acids in males of several species is fixed in the sperm membrane, resulting in improved spermatozoa characteristics. Such enrichment of the cell membrane simultaneously increases the susceptibility of spermatozoa to peroxidation, which in turn has been proposed as one of the major causes of male infertility [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [6][7][8][9] have reported that dietary supplementation with LCP n-3 fatty acids in males of several species is fixed in the sperm membrane, resulting in improved spermatozoa characteristics. Such enrichment of the cell membrane simultaneously increases the susceptibility of spermatozoa to peroxidation, which in turn has been proposed as one of the major causes of male infertility [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…35,36 However, other experiments supplementing boar diets with PUFAs ω-3 and ω-6 improved the quality of seminal characteristics, modifying the fatty acid composition of the sperm. 1,6,7 Although seminal characteristics were not affected by CLA intake during the experimental period, the increase in sperm concentration and viability and the decrease in abnormal morphology may be related to seasonal changes in temperature.…”
Section: Original Researchmentioning
confidence: 99%
“…O ácido linoleico dietético, abundante nos óleos vegetais, é um dos representantes da família n-6, o qual é convertido em ácido aracdônico, precursor das prostaglandinas dienóicas, como a PGF2α. As mesmas enzimas, elongase e dessaturase, que atuam na conversão do ácido linoleico em aracdônico, também convertem o principal ácido graxo n-3, o ácido linolênico a DHA e ácido eicosapentaenóico (EPA), precursor das prostaglandinas trienóicas, como PGF3α (WATHES; ABAYASEKARA; AITKEN, 2007;PAULENZ et al, 1995).…”
Section: áCidos Graxos Poliinsaturados E Antioxidantes Adicionados à unclassified
“…De fato, dietas ricas em AGP de cadeia longa (especialmente n-3) alteraram a proporção de AGP n-3 e n-6 e influenciaram na qualidade seminal, em bodes (DOLATPANAH et al, 2008) e carneiros (SAMADIAN et al, 2010). Entretanto, apesar de suínos terem a proporção de AGP n-6 no sêmen aumentada, não foi observado efeito deste sêmen nas taxas de não retorno (PAULENZ et al, 1995). 87,96 (9,11) 68,50 (7,96) 75,90 (7,93) 82,15 AGP n-6 240,55ab (24,96) 230,40a (21,80) 218,56a (21,73) 299,48b (27,28) 0,07 0,16 0,33 AGP n-3 5,12 (4,47) 11,57 (3,90) 4,97 (3,89) 3,11 (4,88) 0,34 0,61 0,33 Saturados 583,25 (44,40) 573,41 (38,78) 617,06 (38,66) 583,36 (48,53) 0,43 0,32 0,99 Monoinsaturados 92,32 (9,78) 74,57 (8,54) 78,48 (8,52) 91,47 (10,69) 0,12 0,81 0,87 AGP 247,92 (25,03) 246,66 (21,91) 226,21 (21,84) 302,42 (27,42) 0,12 0,14 0,49…”
Section: Quantidades Circulantes De Selênio E áCidos Graxosunclassified
See 1 more Smart Citation